Urease Enzyme and Its Kinetic and Thermodynamic Parameters in Clay Loam Soil - Ekberli , Imanverdi; Kizilkaya, Ridvan; Kars, Nalan (Asian Journal of Chemistry, 2010)
In the present work, urease enzyme activity of clay loam soil (pH 7.1, organic matter 2.26%, C/N ratio 16), kinetic (Vmax, Vm and Vmax/Km) values and thermodynamic (Ea, ΔH, ΔS and ΔG) parameters of this enzyme is determined. For this purpose, kinetic and thermodynamic parameters are calculated by determining urease activity in soil in different substrate concentrations (0, 1, 2, 4, 6, 8, 10 and 12%), incubation periods (0, 1, 2, 3, 4, 5 and 6 h) and incubation temp. (0, 10, 20, 30, 40 and 50ºC). From the results, it is determined that the speed of reaction starts to become static, while substrate concentration reaches to 8% level and becomes static at 10% level and the highest speed of reaction in substrate concentrations occurs at incubation temperature of 50ºC. The highest Vmax, Vm and V max/Km values are determined at 40 and 50ºC and the highest Ea, ΔH and ΔS values are determined in substrate concentration of 10%. It was also determined that ΔG varies between 1.870-2.145 in all substrate concentrations depending on temperature.